Mild Renal Dysfunction and Risk of Thromboembolism and Bleeding in Patients with Atrial Fibrillation: The Chinese Atrial Fibrillation Registry Study - Jingye Li; Sitong Li; Chao Jiang; Jing Du; Xueyuan Guo; Songnan Li; Chenxi Jiang; Ribo Tang; Caihua Sang; Deyong Long; Xin Du; Jianzeng Dong; et al. (Cardiology Discovery)
Abstract. Objective:. Previous studies indicated that patients with atrial fibrillation (AF) and moderate-to-severe chronic kidney disease (CKD) are at a higher risk of thromboembolism and bleeding during anticoagulation. Whether mild CKD is associated with an increased risk of thromboembolism and bleeding in AF patients remains unknown. This study aimed to evaluate the impact of mild CKD on thromboembolism and major bleeding among patients with AF. Methods:. Baseline serum creatinine was available in 17,559 of 25,512 patients enrolled in the China-AF study between August 2011 and December 2018. After excluding those who underwent AF ablation or with moderate-to-severe CKD, 7191 non-valvular AF patients (2059 with mild CKD and 5132 with normal renal function) with regular follow-up for at least 6 months were included. Primary outcomes were the time to the first occurrence of thromboembolic and major bleeding events. Results:. Over a mean follow-up of (44.4 ± 23.4) months, 639 thromboembolism and 231 major bleeding events occurred. The crude incidence rates of thromboembolism were higher in the mild CKD group than that of the normal renal function group (3.0/100 person-years vs. 2.2/100 person-years, P < 0.0001), while the crude incidence rates of major bleeding were comparable between the two groups (1.0/100 person-years vs. 0.8/100 person-years, P = 0.076). After multivariate analyses, mild CKD was not associated with an increased risk of thromboembolism (HR = 1.05, 95% CI: 0.89–1.25, P = 0.547) or major bleeding (HR = 1.11, 95% CI: 0.84–1.47, P = 0.476). Conclusions:. Mild CKD was not an independent risk factor of thromboembolism or major bleeding in patients with AF.